Preparation and Photocatalytic Activity of TiO𝟐-Deposited Fabrics - Yang Xu; Wenzheng Xu; Fenglin Huang; Qufu Wei (International Journal of Photoenergy)
Nanoscale titanium dioxide (TiO2) photocatalytic films were deposited on the surface of polyester nonwovens by using direct current reactive magnetron sputtering. The effects of coating thickness on the surface structures and properties of TiO2-coated fabrics were investigated by X-ray photoelectron spectroscopy (XPS), atomic force microscope (AFM), and scanning electron microscope (SEM). The photocatalytic activity of the functional nonwoven fabrics was evaluated by the degradation of methylene blue. The test results proved that the grain sizes of the sputtered clusters increased and the coating layer became more compact with the increase of film thickness, but the composition of the sputtered films did not have any significant change. At the same time, the photocatalytic activity of TiO2-coated fabrics mostly depended on the film thickness which could lead to the optimum thickness for a particular application.